Accountability, transparency, Participation, and Inclusion. A New Development Consensus? - and Carothers, Thomas; Brechenmacher, Saskia (Carnegie Endowment for International Peace, 2014)
The wide-reaching consensus around the normative and instrumental value of accountability, transparency, participation, and inclusion remains less solid than enthusiasts of these concepts might wish.